PEMBELAJARAN PAI BERBASIS ADAB KONTEKSTUAL - Muthmainnah Muthmainnah; Herawati Herawati (PIONIR: JURNAL PENDIDIKAN, 2021)
This study aims to determine: (1) contextual adab-based education programs, (2) teacher understanding of contextual adab-based PAI learning, and (3) contextual adab-based PAI learning activities at Sukma Bangsa Junior High School, Pidie Regency. This study uses a qualitative approach to analyze the results of research related to contextual adab-based PAI learning through the following techniques: documentation review, direct observation, interviews with school principals, 2 PAI teachers and 6 students as research samples. The results show that: (1) Contextual-based PAI learning implementation programs consist of: 3 books (statutes, blueprints, and guidelines) for student behavior regulations, 5S, 3No, 3 magic words, etc., (2) Teachers understand well the implementation of contextual adab-based PAI learning is characterized by: synergizing cognitive, affective and psychomotor components in the entire learning process and based on the Qur'an and al-Hadith, all parties in schools play a role in implementing contextual adab-based PAI learning, and prioritizing compassion method and nature-based approach in dealing with students who violate ethics, and (3) PAI learning activities based on contextual adab include: using discussion/presentation methods in KBM, supporting programs based on the Al-quran and Al-hadith, familiarizing participants students do routine activities even with a variety of simple activities, etc.